Fermentation of ginseng juice by Lactiplantibacillus plantarum SP055 and Limosilactobacillus fermentum LB-9: Fermentation characteristics and ginsenoside biotransformation pathways - Jianwei Zang; Wei Liu; Chang Xu; Xia Fan; Yibo Shi; Xiaotong Hao; Yimeng Kou; Chunling Meng; Jiamin Xu; Tao Lin; Xin Rui; Dan Gan; et al. (Food Microbiology, 2026)

From fermentation to function: a critical review of lactic acid bacteria redesign for functional foods and precision nutrition - Jianwei Zang; Luyao Xiao; Xiaogan Zhao; Yibo Shi; Kai Ma; Changliang Zhang; Shuo Geng; Xin Rui; Tao Lin; Wei Li (Critical Reviews in Food Science and Nutrition, 2026)

Low-carbon cork agglomerated materials via chitosan/blocked isocyanate adhesive: Cross-linking mechanism, high performance, and life cycle assessment - Jiaxing Zhang; Jingjing Li; Yibo Li; Yifan Yan; Yao Yi; Jing Yuan; Lin Chen; Tonghua Ma; Xiaobing Xie; Zheyun Liu; Shulei Li; Shilin Xu; et al. (Bioresource Technology, 2026)

Biodegradation of cyano liquid crystal monomers by an aerobic enrichment culture: Key degraders and interspecies synergistic mechanisms - Minghan Zhu; Chang He; Shaoyu Tang; Jiayu Zhang; Zhen Yu; Hui Lin; Yibo Yuan; Jonathan W.C. Wong; Hua Yin; Junfeng Niu; Xujun Liang; Zhi Dang (Water Research, 2026)

Electronic configuration regulation and photocatalytic nitrogen fixation performance of the fourth-period d7/d8 metal catalysts - Xiaolu Xu; Jingyi Qu; Yangben Chen; Jiahui Lin; Yibo Zhang; Zhan Hu; Hui Zheng (Journal of Environmental Chemical Engineering, 2026)

Lactobacillus helveticus MB2-1 powders prepared using different drying strategies reshape dominant intermolecular interaction patterns and structural network formation during fermentation of coconut-based yogurt alternatives - Jianwei Zang; Yimeng Kou; Yibo Shi; Xiaotong Hao; Shiyuan Feng; Chunling Meng; Jiamin Xu; Di Yu; Tao Lin; Kai Ma; Changliang Zhang; Mingsheng Dong; et al. (Food and Bioproducts Processing, 2026)

Electron-deficient boron-doped bimetallic (ZnFe) catalyst for high-efficiency photocatalytic nitrogen fixation - Xiaolu Xu; Jiahui Lin; Yangben Chen; Yibo Zhang; Zhan Hu; Jingyi Qu; Zhexiao Zhu; Hui Zheng (Journal of Environmental Chemical Engineering, 2026)

Numerical Simulation of Hydraulic Fracturing in Bedding Reservoir Rocks with Natural Fractures - Li Fan; Yibo Wang; Xiaoning Wang; Shaojiang Wu; Jianghao Lin (Rock Mechanics and Rock Engineering, 2026)

A tropical fermented-food-derived Lactiplantibacillus plantarum SP055 alleviates DSS-induced colitis through coordinated regulation of gut microbiota and intestinal barrier function - Jianwei Zang; Yibo Shi; Xiaotong Hao; Xia Fan; Yimeng Kou; Wanxiang Zhang; Luyao Xiao; Chang Xu; Tao Lin; Xin Rui; Dan Gan; Wei Li (Food Bioscience, 2026)

Humic substances with different molecular weights independently increased antibiotic resistance in agricultural soils contaminated with sulfamethazine - Lanjun Wang; Fangmei Lin; Yuhan Ye; Shuhan Li; Zhen Pan; Yingchao Wu; Yibo Gao; Lusheng Zhu; Jun Wang; Jinhua Wang (Environmental Pollution, 2026)

Resource-efficient numerical computing and elastic wave behavior analysis in complex poroelastic media - Zhitao Zhang; Yuhang Guo; Zhuwen Wang; Baozhi Pan; Yibo Wang; Lin Gan; Wubing Wan; Zhaoqi Sun; Wenqiang Wang; Ruiyi Han; Jiaxu Guo; Yitong Cui (Computers and Geotechnics, 2026)

Octopus-inspired photonic-electronic synergistic hydrogel tactile sensor for accurate and reliable health monitoring - Boqing Jia; Changxu Zhang; Yihe Zhao; Lan Yu; Yibo Lv; Gengyu Han; Xinyu Shi; Zhuorui Chen; Xuanting Lu; Jiaxiang Wang; Min Li; Guoxi Luo; et al. (Chemical Engineering Journal, 2026)

Linking dissolved organic matter sources to greenhouse gas potential in thermokarst lakes of the Qinghai–Tibet Plateau - Wenyan Liu; Zeyong Gao; Chengming Zhang; Fujun Niu; Yibo Wang; Zhanju Lin; Youhua Ran; Jing Luo; Guoan Yin; Yunhu Shang (Cold Regions Science and Technology, 2026)

Impaired Glymphatic-Meningeal Lymphatic Function in Patients with Spontaneous Subarachnoid Hemorrhage - Jianan Lu; Miao Lin; Heping Tian; Yibo Liu; Bingrui Zhu; Jin Mao; Jiahao Zhang; Haocheng Zhang; Sixuan Tian; Xu Li; Ding Xu; Chenhan Ling; et al. (Translational Stroke Research, 2026)

The vinculin-β-catenin axis promotes bone formation and repair: an essential prerequisite for the anti-osteoporotic efficacy of sclerostin-neutralizing antibody - Sixiong Lin; Chu Tao; Yishu Wang; Jianglong Li; YuJia Shi; Qinnan Yan; Yiming Zhong; Huanqing Gao; Tingxuan Wang; Yibo Wang; Qing Yao; Jianmei Huang; et al. (Science China Life Sciences, 2026)

Image-based ice shape and accretion process prediction on wind turbine blades via deep learning with curvature consistency constraint - Jianing Pan; Xin Zhang; Yibo Xi; Kuigeng Lin; Zhenyu Wang (Cold Regions Science and Technology, 2026)

An integrated flotation-cyclic leaching process for reduced acid consumption in vanadium shale extraction - Yibo Hu; Chenkun Lin; Zhiwen Xia; Jianxing Fang; Cong Yin; Qingliang Wang; Huijuan Li; Pengfei Hu (Minerals Engineering, 2026)

GlycoRNA: a new frontier in RNA biology - Yibo Wang; Cong Lin; Xin Li; Xiaohui Wang (Science China Life Sciences, 2026)

Satellite mapping of emperor penguin habitat dispersal under climate extremes - Hong Lin; Xiao Cheng; Jinyang Du; John S. Kimball; Ziyu Yan; Teng Li; Tongwen Li; Yibo Li; Zilong Chen (Remote Sensing of Environment, 2025)

Enhanced photothermal combustion efficiency of propane in the presence of SO2 over Mo-doped Pt/WO3 catalyst: Rational utilization of Ptδ+-(SO4)δ- - Lijing Han; Huimin Chai; Jinliang Lin; Kaiting Chen; Qingwei Li; Qiuhong Zhou; Jun Ye; Hai Liu; Xinyu Han; Zeshu Zhang; Yibo Zhang (Journal of Environmental Chemical Engineering, 2025)

Defect-engineered oriented construction of S-scheme heterojunctions: Efficient photocatalytic performance of NiS-loaded TiO2 nanoflowers - Peng Qiao; Jianwei Zhang; Wenyi Wang; Yijie Lin; Meiru Zheng; Xin Guo; Yibo Liu; Yuanyuan Wang; Jiaojing Zhang; Hua Song; Xueqin Wang (Journal of Environmental Chemical Engineering, 2025)

Fabrication and characterization of starch-based edible films loaded with Lactiplantibacillus plantarum STB9b for pork preservation - Jianwei Zang; Yue Hu; Tao Lin; Xia Fan; Yimeng Kou; Yibo Shi; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Xin Rui; Wei Li (Food Packaging and Shelf Life, 2025)

Flux measurements of NOx, O3 and Ox: Emission characteristics, inventory validation and titration effects - Xiaoxiao Zhang; Bin Yuan; Yibo Huangfu; Huizhi Liu; Thomas Karl; Ming Chang; Shiyi Chen; Tao Song; Jintai Lin; Guannan Geng; Hongjuan Li; Eran Tas (Environmental Pollution, 2025)

Numerical analysis on energy and exergy performance of cascade electrical-temperature vacuum swing adsorption (C-ETVSA) for direct air capture: A parametric effect study - Lanlan Zhang; Jiayu Lin; Yongzhen Wang; Kai Han; Baojun Tang; Yibo Han; Junyao Wang; Long Jiang (Journal of Cleaner Production, 2025)

Unraveling phylogenetic conflicts and adaptive evolution in Chiroptera using large-scale mitogenomes and nuclear genes - Dengfeng Guan; Xin Huang; Guangping Huang; Jiang Zhou; Lin Yang; Wenhua Yu; Weijian Guo; Jiang Feng; Yi Wu; Yibo Hu; Fuwen Wei (Science China Life Sciences, 2025)

Immunomodulatory effect of Qihuang Biwen decoction and its postbiotic product - Junxiang Li; Mingqian Wang; KangKang Liu; Yibo Liang; Haijuan Wang; Yang Lin; Zeqi Huo; Zhiming Zhang; Chunjiang Zhang (World Journal of Microbiology and Biotechnology, 2025)

Electro-pulsation-generated variable-valent metal triggers alternate pesticide oxidation-chlorinated byproduct reduction on ruthenium-single-atom electrode - Yangqi E; Binyao Wang; Yibo Lin; Huachang Jin; Xueming Chen; Jianmeng Chen; Jin Hur; Yang Yu; Dongzhi Chen (Journal of Hazardous Materials, 2025)

The cost and benefit of synergistic emission reduction of CO2 and non-CO2 greenhouse gases in the industrial sector in the context of carbon neutrality - Sihan Lin; Yuehan Wang; Li Li; Yalin Lei; Sanmang Wu; Yibo Wang; Fujie Yang; Zengchuan Wang; Yanfang Cui (Journal of Cleaner Production, 2025)

A stable dual-functional monomer imprinted polymer platform for electrochemical sensitive detection of PFAS - Xingyang Cheng; Jing Tang; Yu Chen; Xue Bai; Yibo Liao; Xilian Ouyang; Yuchen Wang; Lin Tang (Journal of Hazardous Materials, 2025)

Widespread microplastic and nanoplastic contamination in the intestines of birds: A case study from Chengdu, China - Pinxi Zhou; Mengzhu Wang; Shane DuBay; Yiwei Cao; Shangmingyu Zhang; Jiayu Zhang; Zhengrui Hu; Zhixiong Yang; Yibo Wang; Xiaoying Zhao; Lin Sun; Jiachen Dang; et al. (Journal of Hazardous Materials, 2025)

Improving in-situ spectral estimation of wetland soil organic carbon by integrating multiple optimization strategies - Hongyi Li; Jiangtao Yang; Bifeng Hu; Yibo Geng; Qian Zhu; Yongsheng Hong; Yi Lin; Jie Peng; Wenjun Ji; Songchao Chen; Zhou Shi (CATENA, 2025)

Extreme degradation of alpine wet meadow decelerates soil heat transfer by preserving soil organic matter on the Qinghai–Tibet Plateau - Zeyong Gao; Chengming Zhang; Wengyan Liu; Fujun Niu; Yibo Wang; Zhanju Lin; Guoan Yin; Zekun Ding; Yunhu Shang; Jing Luo (Journal of Hydrology, 2025)

Exposure profiles, determinants, and health risks of chemicals in personal care products among healthy older adults from the China BAPE study - Xiaojie Guo; Jiankun Qian; Huimin Ren; Enmin Ding; Xiao Ma; Jiran Zhang; Tian Qiu; Yifu Lu; Peijie Sun; Chenfeng Li; Chenlong Li; Yibo Xu; et al. (Journal of Hazardous Materials, 2025)

Advancements in rapid on-site detection of chemical oxygen demand: Insights into sensing mechanisms and practical applications - Xingyang Cheng; Jing Tang; Yu Chen; Yibo Liao; Zhigang Yi; Pansong Li; Lin Tang (Chemical Engineering Journal, 2025)

Multi-USV cooperative target encirclement through learning-based distributed transferable policy and experimental validation - Chenming Zhang; Rijie Zeng; Bin Lin; Yibo Zhang; Wei Xie; Weidong Zhang (Ocean Engineering, 2025)

Quantifying the effects of wind wave on cyanobacterial blooms in large shallow lake from 10 years high frequency satellite observation - Minsha Guan; Yunlin Zhang; Wei Li; Na Li; Lin Qi; Kun Shi; Yibo Zhang; Boqiang Qin; Changchun Huang (Hydrobiologia, 2025)

Genome-wide analysis of DNA methylation and gene expression in large yellow croaker (Larimichthys crocea) under hypoxic stress - Zhenyu Gao; Chenyu Zheng; Yibo Zhang; Jian Yang; Xuelei Wang; Lin Huang; Xiongfei Wu; Jie Ding; Junquan Zhu; Weiliang Shen (Aquaculture, 2025)

N6-methyladenosine RNA methylation regulates microplastics-induced cell senescence in the rainbow trout liver - Fang Ma; Zhe Liu; Jinqiang Quan; Yijun Yuan; Jianzhou Wang; Xiangjun Zhou; Jing Wang; Lei Shen; Dunting Tie; Minlan Yang; Yang Lin; Guoyu Song; et al. (Science of The Total Environment, 2025)

Experimental study on shear mechanism of a new TU-type connector at HSS-UHPC interface - Yangqing Liu; Yibo Zhao; Haiyan Yang; Xiaoqing Xu; Weiwei Lin; Xiaoqing Du; Yuqing Liu (Engineering Structures, 2025)

SoxB family genes delay regeneration and cause abnormal movement in Dugesia japonica - Yibo Yang; Ziyi Lin; Nannan Li; Ning Li; Dezeng Liu; Zimei Dong; Guangwen Chen (Molecular Genetics and Genomics, 2024)

Protective Role of (-)-Epicatechin on Trimethylamine-N-Oxide (TMAO)-Induced Cardiac Hypertrophy via SP1/SIRT1/SUMO1 Signaling Pathway - Siting Hong; Jing Lu; Jiaoyan Li; Yingchun Luo; Dongxue Liu; Yuanyuan Jin; Zeng Wang; Yibo Wang; Hao Zhang; Xin Zhang; Yang Li; Haoruo Zhang; et al. (Cardiovascular Toxicology, 2024)

Experimental Study on Deformation and Passive Earth Pressure Behind Cantilever Pile Retaining Walls in Narrow Excavations - Weidong Hu; Tao Hu; Sichen Lin; Jinggan Tang; Yibo Zhou; Qisheng Hu (Geotechnical and Geological Engineering, 2024)

Personal exposure to airborne organic pollutants and lung function changes among healthy older adults - Xiaojie Guo; Huimin Ren; Peijie Sun; Enmin Ding; Jianlong Fang; Ke Fang; Xiao Ma; Chenfeng Li; Chenlong Li; Yibo Xu; Kangning Cao; Elizabeth.Z. Lin; et al. (Environmental Research, 2024)

Boron isotopic compositions of middle Miocene to recent shallow-water carbonates from the South China Sea: Assessing diagenetic effects and implications for paleoclimate changes - Xinran Chen; Feifei Zhang; Yibo Lin; Mengchun Cao; Haizhen Wei; Changgui Xu; Caiwu Fan; Shu-zhong Shen (Global and Planetary Change, 2024)

Fe/Mn (oxyhydr)oxides reductive dissolution promoted by cyanobacterial algal bloom-derived dissolved organic matter caused sediment W release during an algal bloom in Taihu Lake - Juan Lin; Xiang Chen; Yvlu Liu; Yibo Wang; Jinxia Shuai; Musong Chen (Water Research, 2024)

Erratum to: Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2024)

Improved bacterial composition and co-occurrence patterns of rhizosphere increased nutrient uptake and grain yield through cultivars mixtures in maize - Xucun Jia; Haipeng Shang; Yibo Chen; Mengjie Lin; Yuepeng Wei; Yuxia Li; Rongfa Li; Pengfei Dong; Yinglong Chen; Yongen Zhang; Qun Wang (Science of The Total Environment, 2024)

Vibration anomaly detection of wind turbine based on temporal convolutional network and support vector data description - Kuigeng Lin; Jianing Pan; Yibo Xi; Zhenyu Wang; Jianqun Jiang (Engineering Structures, 2024)

Flexible piezoelectric sensor based on PAN/MXene/PDA@ZnO composite film for human health and motion detection with fast response and highly sensitive - Yan Huang; Sixian Chen; Yi Li; Qianbing Lin; Yibo Wu; Qisong Shi (Chemical Engineering Journal, 2024)

Artificial humic acid coated ferrihydrite strengthens the adsorption of phosphate and increases soil phosphate retention - Shuang Gai; Bing Liu; Yibo Lan; Lin Han; Yixiong Hu; Guanghao Dongye; Kui Cheng; Zhuqing Liu; Fan Yang (Science of The Total Environment, 2024)

A versatile CuCo@PDA nanozyme-based aptamer-mediated lateral flow assay for highly sensitive, on-site and dual-readout detection of Aflatoxin B1 - Xu Zhu; Jing Tang; Xilian Ouyang; Yibo Liao; Haopeng Feng; Jiangfang Yu; Li Chen; Yating Lu; Yuyang Yi; Lin Tang (Journal of Hazardous Materials, 2024)

Distribution and sources of polycyclic aromatic hydrocarbons in surface sediments of the East China marginal seas: Significance of the terrestrial input and shelf mud deposition - Qi Shen; Huimin Yu; Yibo Cao; Zhigang Guo; Limin Hu; Lian Duan; Xueshi Sun; Tian Lin (Marine Pollution Bulletin, 2024)

A comprehensive exploration of characteristics and source attribution of carbonaceous aerosols in PM2.5 in an East China megacity - Lian Duan; Huimin Yu; Qiongzhen Wang; Fengwen Wang; Tian Lin; Yibo Cao; Zhigang Guo (Environmental Pollution, 2024)

Determination of effects of thermophilic and hyperthermophilic temperatures on anaerobic hydrolysis and acidogenesis of pig manure through a one-year study - Min Lin; Wei Qiao; Lijuan Ren; Yibo Sun; Jiahao Zhang; Renjie Dong (Bioresource Technology, 2024)

The mediating effect of perceived stress on the relationship between big five personality traits and suboptimal health status in Chinese population: a nationwide survey in the framework of predictive, preventive, and personalized medicine - Qihua Guan; Hualei Dong; Zhihui Zhang; Zheng Guo; Zi Lin; Hui Niu; Yibo Wu; Haifeng Hou (EPMA Journal, 2023)

Bending moment characteristic analysis of utility-scale onshore wind turbine blades based on monitoring data - Yibo Xi; Kuigeng Lin; Jianing Pan; Liyun Sun; Hao Li; Zhenyu Wang (Engineering Structures, 2023)

Experimental study on predicting head-cut migration rate of check dams - Yibo Shan; Qiming Zhong; Shengshui Chen; Lin Wang; Xiaokang Chen; Shengyao Mei; Meng Yang (Journal of Hydrology, 2023)

Degradation mechanisms of 2-chlorophenol by Acinetobacter sp.: Exploring cellular membrane structure, intra- and extracellular components, and transcriptomic analysis - Han Lin; Wenqi Guan; Yibo Xiao; Yujiao Qu; Yuan Ren (Journal of Environmental Chemical Engineering, 2023)

Construction of a spatially gridded heat flux map based on airborne flux Measurements using remote sensing and machine learning methods - Yibo Sun; Li Jia; Qiting Chen; Xingwen Lin; Bilige Sude; Zhanjun Quan; Ronald W.A. Hutjes (Agricultural and Forest Meteorology, 2023)

PM2.5-bound polycyclic aromatic hydrocarbons of a megacity in eastern China: Source apportionment and cancer risk assessment - Lian Duan; Huimin Yu; Qiongzhen Wang; Yibo Cao; Guochen Wang; Xueshi Sun; Hao Li; Tian Lin; Zhigang Guo (Science of The Total Environment, 2023)

Synergistic effects of biochar and carboxymethyl cellulose sodium (CMC) applications on improving water retention and aggregate stability in desert soils - Fanfan Shao; Senlin Zeng; Quanjiu Wang; Wanghai Tao; Junhu Wu; Lijun Su; Haokui Yan; Yibo Zhang; Shudong Lin (Journal of Environmental Management, 2023)

Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2023)

Ecological niche complexity of invasive and native cryptic species of the Bemisia tabaci species complex in China - Yantao Xue; Congtian Lin; Yaozhuo Wang; Yibo Zhang; Liqiang Ji (Journal of Pest Science, 2022)

A Preliminary Study on Silver Isotopic Composition in Polymetallic Ore Deposits in Eastern China - Ge Dong; Hai-Zhen Wei; Yuanfeng Zhu; Xi Liu; Qi Guo; Wei Pu; Yibo Lin; Junlin Wang (Journal of Earth Science, 2022)

Differential Affinities of a Pocillopora damicornis Galectin to Five Genera of Symbiodiniaceae at Different Temperatures - Xingjuan Wang; Zhongjie Wu; Yibo Wu; Mingxun An; Zhi Zhou; Senjie Lin (Frontiers in Marine Science, 2021)
The symbiosis of coral-Symbiodiniaceae is the quintessential basis of the coral reef ecosystem, and its breakdown results in coral bleaching, one of the most severe ecological catastrophes in the ocean. Critical to the establishment of the symbiosis is the host’s specific recognition of the symbionts through the binding of the coral host’s pattern recognition receptors (PRRs) to the symbiont cell surface’s glycoconjugates. However, the molecular basis for this recognition process is poorly understood. The present study investigated the binding affinities of the coral galectin PdGLT-1 to different symbiodiniacean species under different temperatures. At 25°C, the PdGLT-1 recombinant protein (rPdGLT-1) exhibited different binding affinities to different symbiodiniacean species from five genera, with a significantly higher binding affinity ( p < 0.05) to Fugacium kawagutii (2.6-fold) and Cladocopium goreaui (1.9-fold) than Symbiodinium microadriaticum . The binding topology of rPdGLT-1 differed among the five symbiodiniacean species; for S. microadriaticum , Breviolum minutum , and Durusdinium trenchii , the binding was on some specific sites on the cell surface, whereas for C. goreaui and F. kawagutii , the binding signals were detected over the whole cell surface. Interestingly, PdGLT-1 binding induced agglutination of F. kawagutii cells but not of C. goreaui , explaining why C. goreaui was the most dominant symbiodiniacean symbionts in corals. Moreover, the affinity of rPdGLT-1 to Symbiodiniaceae was affected by temperature, and the highest binding affinities were observed at 30, 20, 30, 35, and 30°C for S. microadriaticum , B. minutum , C. goreaui , D. trenchii , and F. kawagutii , respectively. The optimal binding temperatures were consistent with the current understanding that D. trenchii was the most thermal resistant among these species. These results suggest that the binding affinity of the PRR PdGLT-1 may determine the specificity of host-symbiont pairing and explain why Cladocopium is the dominant symbionts of coral P. damicornis at normal temperature, and corals with Durusdinium symbionts may survive better at high temperature.

Molecular characterization and gene expression analysis of tomato WOX transcription factor family under abiotic stress and phytohormone treatment - Hui Li; Xiaohong Li; Meihua Sun; Shuisen Chen; Hui Ma; Jingwei Lin; Yibo Sun; Ming Zhong (Journal of Plant Biochemistry and Biotechnology, 2021)

Back analysis of breaching process of Baige landslide dam - Qiming Zhong; Shengshui Chen; Lin Wang; Yibo Shan (Landslides, 2020)

Coupling virio- and bacterioplankton populations with environmental variable changes in the Bohai Sea - Caixia Wang; Lin Wu; Yibo Wang; James S. Paterson; James G. Mitchell; Xiaoke Hu (Acta Oceanologica Sinica, 2020)

Root-induced changes to soil water retention in permafrost regions of the Qinghai-Tibet Plateau, China - Zeyong Gao; Fujun Niu; Yibo Wang; Zhanju Lin; Jing Luo; Minghao Liu (Journal of Soils and Sediments, 2018)

Creating the Livestock Guru: ICTs to enhance livestock-related knowledge among poor households in Orissa, India - Yibo Lin; Claire Heffernan (Tropical Animal Health and Production, 2010)